MODEL KOMUNIKASI MUALLIM DI PONDOK PESANTREN NURUL IMAN DALAM MEMBERIKAN PEMBELAJARAN KEPADA SANTRI DI DESA SILAU DUNIA KECAMATAN SILAU KAHEAN KABUPATEN SIMALUNGUN - Aziz, Abdul; Susanti, Neila; Anas Azhar, Anang (Lafadz Jaya Publisher, 2023)
This study aims to find out how the Muallim communication model provides learning to students at Pondok Pesantren Nurul Iman Silau Dunia. Researchers use persuasive communication theory as a means to connect problems and theory. The type of research used is field research. Researchers make observations about phenomena in a scientific situation to produce in-depth descriptive data using qualitative data analysis techniques where the process of systematically searching and compiling data obtained from interviews, field notes and other materials so that it is easy to understand so that it can be informed to people other. So the results of the communication model used by the Islamic teacher in providing learning to students at the Nurul Man Islamic Boarding School, is to use interpersonal communication, then the way the teacher teaches students to read extensively using group communication, interpersonal communication and persuasive communication. The methods and processes in conveying mu'alim learning to students at the Nurul man Islamic boarding school are the sorogan method, the wetonan or bendongan method, the rote method (tahfidz), the discussion method, the majlis taklim method and the method of writing scientific papers.